Ultrathin, flexible, and high-strength Ni/Cu/metallic glass/Cu/Ni composite with alternate magneto-electric structures for electromagnetic shielding. (10th August 2021) - Ma, Zenan; Li, Jiawei; Zhang, Jijun; He, Aina; Dong, Yaqiang; Tan, Guoguo; Ning, Mingqiang; Man, Qikui; Liu, Xincai
Graphical abstract: Highlights: Ni/Cu/MG multilayer composite with alternate magnetic and electrical structures was designed. Ni/Cu/MG exhibits EMI SE of 35 dB at an ultrathin thickness of 0.02 mm. Ni/Cu/MG displays excellent flexibility, superior tensile strength and bending stability. Ni/Cu/MG has excellent Joule heating characteristics and thermal stability. Abstract: Electromagnetic interference (EMI) shielding materials with ultrathin, flexible, superior mechanical and thermal management properties are highly desirable for smart and wearable electronics. Here, ultrathin and flexible Ni/Cu/metallic glass/Cu/Ni (Ni/Cu/MG) multilayer composite with alternate magnetic and electrical structures was designed via facial electroless plating of Cu and Ni on an Fe-based metallic glass. The resultant 0.02 mm-thick Ni/Cu/MG composite displays a superior EMI shielding effectiveness (EMI SE) of 35 dB and a great EMI SE/t of 1750 dB/mm, which is greater than those of composites with monotonous multilayer or homogeneous structures. The improved EMI SE originates from the massive ohmic losses, the enhanced internal reflection/absorption, and the abundant interfacial polarization loss. Particularly, Ni/Cu/MG exhibits a high tensile strength of up to 1.2 GPa and outstanding mechanical stability, enabling the EMI SE remains unchanged after 10, 000 times of bending. Moreover, Ni/Cu/MG has excellent Joule heating characteristics and thermal stability, which is very suitable for heating components of wearable hyperthermia devices.